Female researchers in high-impact psychiatric journals: What do they focus on? - Trimmel, Melanie; Amering, Michaela; Suessenbacher-Kessler, Stefanie; Schrank, Beate; Gmeiner, Andrea (Frontiers in Psychiatry, 2023)
The regular analysis of publication trends, including gender aspects, is an important contribution to the identification of gender-specific differences in academic psychiatry. The present study aimed to characterise publication topics in three high-impact psychiatric journals across three time points within 15 years (2004, 2014 and 2019). Publication patterns of female authors compared to their male colleagues were examined. All articles published in 2019 in the three high-impact psychiatry journals JAMA Psychiatry, British Journal of Psychiatry and American Journal of Psychiatry were included and compared with data from the 2004 and 2014 assessments. Descriptive statistics were calculated and Chi-square tests were performed. In 2019, a total of 473 articles were published, 49.5% were original research articles, of which 50.4% were published by female first authors. The results of this study showed a stable trend in the publication of research on mood disorders as well as schizophrenia and psychotic disorders in high-ranking psychiatric journals. Although the percentage of female first authors in the three most common target populations under study (mood disorders, schizophrenia and general mental health) increased from 2004 to 2019, gender equality has not yet been achieved in these fields. However, in the two most frequent subject matters, basic biological research and psychosocial epidemiology, the percentage of female first authors was more than 50%. Consistent monitoring of publication trends and gender distribution by researchers and journals in psychiatric research should be continued to identify and counteract the possibility of the underrepresentation of women in certain fields.